Characterizing Iranian Pediatric Patients With Relapsed Acute Lymphoblastic Leukemia Through Gene Expression Profiling of Common ATP Binding Cassette Transporters Subfamily C. Issue 1 (January 2020) - Mehrvar, Narjes; Abolghasemi, Hassan; Rezvany, Mohammad R.; Akbari, Mohammad E.; Saberynejad, Javad; Mehrvar, Azim; Movafagh, Abolfazl
Abstract : Background: The correlation between gene expression of ABCC transporters and recurrence as a treatment failure in pediatric patients with acute lymphoblastic leukemia (ALL) is an unsolved problem in scientific associations. The aim of this study was to evaluate the predictive value of ABCC1-6 gene expression pattern for estimating recurrence in Iranian pediatric patients with ALL. Materials and Methods: Iranian pediatric patients with approved ALL enrolled in this study as 2 groups of case (relapsed ALL) and control (treated individuals who lasted for >3 years following their final treatment). Real-time polymerase chain reaction was done with GAPDH for expressing ABCC1-6 transporter genes. Cumulative doses of Vincristine, Daunorubicin, and L-Asparginase were checked for each patient. Gathered data analyzed with SPSS version 22 and REST 2009 software. Results: Thirty-nine samples as 23 relapsed ALL and 16 controls enrolled. High expression of ABCC2-6 and low expression of ABCC1 were detected in pediatric patients with relapse. ABCC3 and ABCC4 had significant relation with high-risk patients of NCI group. Also, ABCC4 and ABCC6 had more expression with high doses of Daunorubicin and L-Asparginase. Conclusions: Designed expression pattern have the predictive value for estimating of conferring relapse in Iranian pediatric patients with diagnosed ALL. The authors suggest of designing a multiple childhood malignancy center project to evaluate this pattern in a cohort study.